2014
DOI: 10.4253/wjge.v6.i4.105
|View full text |Cite
|
Sign up to set email alerts
|

Childhood achalasia: A comprehensive review of disease, diagnosis and therapeutic management

Abstract: Achalasia is an esophageal motility disorder characterized by failure of lower esophageal sphincter (LES) relaxation and is rare in children. The most common symptoms are vomiting, dysphagia, regurgitation, and weight loss. Definitive diagnosis is made with barium swallow study and esophageal manometry. In adults, endoscopic biopsy is recommended to exclude malignancy however; it is not as often indicated in children. Medical management often fails resulting in recurrent symptoms and the ultimate definitive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 49 publications
0
90
0
6
Order By: Relevance
“…[13] Most studies in children have supported using surgical Heller's myotomy for long-term outcomes since the introduction of minimal surgical techniques. [5,[14][15][16][17] Recently, endoscopic peroral esophageal myotomy (POEM) has also been described. Inoue H. et al performed the first POEM in adults in 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Most studies in children have supported using surgical Heller's myotomy for long-term outcomes since the introduction of minimal surgical techniques. [5,[14][15][16][17] Recently, endoscopic peroral esophageal myotomy (POEM) has also been described. Inoue H. et al performed the first POEM in adults in 2008.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Until now, laparoscopic Heller's myotomy has been considered the treatment of choice for achalasia in adults and children with excellent longterm results. [14][15][16][17] Conventional two-dimensional laparoscopic procedures lack the flexibility of instruments and the highquality three-dimensional imaging that are facilitated by the robot, especially in a narrow operation field with the need for advanced intracorporeal suturing. [2,5] In addition to these advantages, robotic surgery provides motion scaling with the elimination of hand tremors.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by failed relaxation of the lower esophageal sphincter (LES) and absent peristalsis of the distal esophagus. The distinctive symptoms of pediatric achalasia are dysphagia, regurgitation, vomiting, respiratory symptoms (nocturnal cough, aspiration), retrosternal pain, and weight loss [3]. All therapeutic options focus on reducing the pressure gradient across the LES, and this can be achieved by pharmacological agents, endoscopic methods (botulinum toxin injection, balloon dilation, stent insertion) and surgical myotomy (open or laparoscopic) [3].…”
mentioning
confidence: 99%
“…It is suggested that the cause of achalasia is ischemia following excessive rotation of the gut as a volvulus in utero in the embryo which selectively destroys ganglion cells [9]. Other tissues recover but neurons do not regenerate, leaving denervated gut forever.…”
Section: Embryologymentioning
confidence: 99%